HUBUNGAN TINGKAT KECEMASAN PASIEN RADIOTERAPI TERHADAP COVID-19 YANG MEMPENGARUHI KUNJUNGAN PASIEN RADIOTERAPI SELAMA PANDEMI COVID-19 - Situmorang, Ronaldo; Jamnasi, Juli; Sitompul, Donald F (Jurnal Kedokteran Methodist, 2022)
Background : Cancer is the number one cause of death in the world. Of the 10.9 million people diagnosed with cancer worldwide each year, about 50% require radiotherapy. The use of radiotherapy is still not widely used and is still limited in Indonesia. Due to the pandemic, patients are anxious about COVID-19 infection, so there are some patients who delay treatment to the hospital because the hospital is considered a place with a high transmission rate. The correlation between radiotherapy patient anxiety towards COVID-19 infection with radiotherapy patient visits during the COVID-19 pandemic at Vina Estetica General Hospital. Research Objectives: This study aims to determine the relationship between radiotherapy patient anxiety and COVID-19 infection with radiotherapy patient visits during the COVID-19 pandemic at the Vina Estetica General Hospital. Research Methods: The type of research that used in this study is analytical research. The analytical research approach uses a cross sectional study approach, where the observations of the variables are only for a moment and one observation during the study. The research was done at RSU Vina Estetica Medan with a minimum sample size of 44 people. Results: The results showed that the majority of patients had a mild level of anxiety about COVID-19, which was 70.45% of the total patients or 31 people. A total of 8 (18.18%) patients had moderate anxiety, 3 (6.82%) had severe anxiety, and 2 patients (4.55%) did not feel anxious. The majority of the patients (93.18%) did not delay the radiotherapy visit. Only 3 people (6.82%) were found to delay radiotherapy visits. Conclusion: There is no correlation between the anxiety level of radiotherapy patients and the number of visits